Eletrocardiografia de cães submetidos a diferentes concentrações de desflurano, pré-tratados ou não com a associação de fentanil/droperidol - Santos, Paulo Sérgio Patto Dos; Nunes, Newton; Vicenti, Felipe Antônio Mendes; Martins, Silvio Emílio Cuevas; Rezende, Márlis Langenegger De (Universidade Federal de Santa Maria, 2001)
The aim of this work was to evaluate the effects of the fentanil/droperidol association over the heart rate (HR) and electrocardiography (ECG) of dogs submitted to anesthesia by desflurane. For that, forty healthy adult dogs, males and females were used. The dogs were equally separate in two groups G1 and G2. G1 received fentanil (15.7mg/kg) associated to droperidol (0.5mg/kg); while G2 received saline solution at 0.9% (placebo), both applied intravenously. After 15 minutes the general anesthesia was induced with intravenously administration of propofol (5mg/kg). The dogs were submitted to inhalatory anesthesia with desflurane, with an initial concentration of 1.6 MAC. The observations of the variables were begun immediately before the application of the agents (M1). New measurings were carried out 15 minutes after the administration of the fentanil/droperidol association or placebo (M2) and 20 minutes after the anesthetic induction (M3). The other measurings coincided with the establishment of the concentrations of 1.4; 1.2 and 1.0 MAC, respectively M4 to M6. The numeric data were submitted to the Analysis of Profile, being considered the level of significance of p<0.05. The results allowed to conclude that the fentanil/droperidol association decreases HR and the desflurane blocks the decrease on HR produced by the association and promoves a delay in the electrical atrial and ventricular conduction.

Avaliaram-se os efeitos da associação de fentanil e droperidol sobre a freqüência cardíaca (FC) e eletrocardiografia (ECG), em cães submetidos à anestesia pelo desflurano. Para tal, foram empregados quarenta animais hígidos, adultos, machos e fêmeas, com peso variando entre 6,5 e 20kg. Os cães foram separados igualmente em dois grupos G1 e G2. Ao G1, administrou-se fentanil (15,7mg/kg) associado ao droperidol (0,5mg/kg); ao G2, administrou-se solução fisiológica a 0,9% (placebo), ambos por via intravenosa. Decorridos 15 minutos, induziu-se à anestesia geral com administração intravenosa de propofol (5mg/kg). Ato contínuo, os cães foram submetidos a anestesia inalatória pelo desflurano, diluído em oxigênio, através de circuito anestésico semifechado na concentração inicial de 1,6 CAM. As observações das variáveis tiveram início imediatamente antes da aplicação dos fármacos M1. Novas mensurações foram realizadas 15 minutos após a administração da associação fentanil/droperidol ou placebo M2 e 20 minutos decorridos da indução anestésica M3 (1,6 CAM). As demais colheitas coincidiram com o estabelecimento das concentrações de 1,4; 1,2; e 1,0 CAM, respectivamente M4 a M6. Os dados numéricos destas variáveis foram submetidos à Análise de Perfil, sendo considerado o nível de significância de p<0,05. Os resultados permitiram concluir que a associação de fentanil/droperidol reduz a freqüência cardíaca e o desflurano bloqueia a bradicardia produzida pela associação e promove retardo na condução elétrica atrial e ventricular.
Electrocardiography of dogs undergoing different desflurane concentrations, premedicated or not with fentanyl/droperidol association
Keywords: electrocardiography; MAC; desflurane; fentanyl; droperidol; dogs; eletrocardiografia; CAM; desflurano; fentanil; droperidol; cães